Utilizing an I-shaped shear link as a damper to improve the behaviour of a concentrically braced frame. (November 2021) - Ghamari, Ali; Kim, Young-Ju; Bae, Jaehoon
Abstract: Over the past few decades, concentrically braced frames (CBFs) have become a commonly used load-resistant bearing system in steel structures. CBF systems have high lateral stiffness and lateral strength; however, they have low ductility and a low seismic energy dissipating capacity. Under seismic loading, the diagonal elements of a CBF system are susceptible to buckling, causing hysteresis in the compression zone and severely reducing energy absorption. Although steel dampers improve the hysteretic behaviour of the braces, they impose additional costs on structures. Therefore, in this study, an I-shaped steel damper with a shear yield mechanism was introduced; this is an economical solution, has a simple construction, and can be easily replaced after an earthquake. The proposed damper was evaluated numerically and parametrically. Results indicate that the proposed damper acts as a ductile fuse that prevents buckling of the diagonal element of a CBF system. It was found that both the web and flange plates contribute to the shear resistance, with the flange carrying approximately 15% of the shear force, as expressed in the presented equations. Additionally, overstrength obtained for the damper was greater than 1.5 (proposed by AISC). Necessary relations are represented to predict and design the damper and the elements outside it. Graphical abstract: Unlabelled Image Highlights: An innovative I-shaped link as a damper with shear mechanism is proposed. The damper acts as a ductile fuse that prevents the nonlinear behavior of the CBF system. Relations to design of the damper and elements outside the damper are presented.